Yellow River Basin Management under Pressure (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Ecological protection and high-quality development in the basin of the Yellow River, known as China’s “Mother River” and “the cradle of Chinese civilization”, have been receiving increasing attention because of the important role they play in China’s economic and social development, and its cultural heritage. Under ongoing climate change and intense human activities, the Yellow River basin is facing crucial challenges, e.g., flooding, water security, water resource shortage, water pollution, and ecological environment degradation, which seriously affects the sustainable development of the regional economy and society. Meanwhile, significant differences in key characteristics across the upper, middle, and lower reaches call for joint management efforts, including integrated management, water conservancy, and ecological environment restoration. This Special Issue focusses on the current state, challenges, and suggestions relating to Yellow River basin management and sustainable development under pressure, aiming to help improve ecological protection and achieve high-quality development. The following topics, including the management, restoration and protection of the Yellow River basin, and harmonious regulation of the human–water relationship were systematically studied.